(untitled) (Research, Society and Development, 2020)
Objective: Analyze from scientific publications how health care is expressed in the daily lives of children with stomas. Method: Integrative review of scientific literature carried out between the years 2009 to 2019, in the databases Medical Literature Analysis and Retrieval, Latin American and Caribbean Literature in Health Sciences and Databases of Nursing, using the keywords: stomas, child and health care. Analysis and Results: The sample consisted of eight articles and two categories built for analysis: care for ostomized children inside the family and the context of care for ostomized children from the perspective of health and education professionals. Conclusion: There were few productions related to the investigated thematic. However, gets registered the importance of valuing the complete health care for the ostomized children, in the perspective of consolidating the Unified Nacional Health System.